A geochemical study of the main valleys’ waters on the left part of Mosul (Iraq) - Ibrahim, Iman F.; Al-Youzbakey, Kotayba T. (Italian journal of engineering geology and environment, 2023)
Increases in population and the expansion of industrial and agricultural operations result in an increase in agricultural and industrial trash as well as residential waste that is dumped directly into rivers and streams. These pollutants typically pollute river or stream water. This study focuses on the effects of domestic, industrial, and agricultural waste water on the water quality of the five main valleys in the left part of Mosul City: Al-Rashediya, Al-Kharrazi, Al-Khosar, Al-Danffilli, and Al-Shoar. Forty-eight samples of the water from these valleys were measured in the field for their physical characteristics (pH, EC, TDS, and Tr). The chemical properties (Ca2+, Mg2+, Na+, K+, HCO3-, SO42-, Cl- and NO3-), the heavy elements (Fe, Cu, Pb, Co and Mn) and the organic maters, were analyzed. The results indicated that calcium and bicarbonate are more abundant than other cations and anions, respectively. This mainly indicates the impact of carbonate fragment contents and calcareous cementing materials in the soils that exposed to chemical weathering in the outcrops on water quality. Heavy element pollution factors {The heavy metal pollution index (HPI), Heavy metals rating index (HEL), Metal Index (MI), and Contamination Index (Cd)} generally indicated that the water in the study area is highly polluted and unsuitable for agricultural use. The amounts of pollutants in the rivers of Al-Shoar and Al-Danffilli valleys appear to be higher than those of the other valleys since these valleys are generally the most exposed to waste, especially industrial waste.